The moral of Si Tanggang's tale rings true in Belagavi - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
What has Si Tanggang got to do with the place? What was he doing there? Well, it all started with a campus where Universiti Sains Malaysia (USM) started its “off shore” medical campus in Belagavi (a city in the southwest Indian state of Karnataka), in partnership with the local Karnataka Lingayat Education (KLE) University there a decade ago in 2009. It was spurred by the need to cope with the heightened demand from qualified medical applicants for places at the USM Medical campus in Kelantan. Broached by KLE, the idea was quickly realised when the USM-KLE International Medical Programme (IMP) was set up to become the pride of both institutions with a difference. Thus far it has graduated almost 500 students who were fully integrated with their fellow alumni from the Kelantan campus.